2014
DOI: 10.12963/csd.14177
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Boston Naming Test in Differentiating between Mild Cognitive Impairment and Normal Elderly: A Meta-Analysis

Abstract: Objectives:The Boston Naming Test (BNT) is a widely used neuropsychological test for evaluating language ability and mild cognitive impairment (MCI). Several different abbreviated forms of the BNT have been used in previous research and clinical settings. For efficiency, valid and sensitive abbreviated forms of the BNT are useful. However, there has been no study that focused on comparison among various forms of the BNT and MCI. Thus, we conducted a meta-analysis of studies that assessed subjects with MCI alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…Complaints of difficulty in finding words are common in the elderly, and are even more common and challenging in elderly individuals with MCI [2,3]. However, studies of the differences in performance between individuals with MCI and healthy elderly (HE) subjects have reported mixed findings [4,5,6,7,8,9,10,11,12,13,14]. Evaluation of naming ability in individuals with MCI requires the consideration of a number of factors and characteristics affecting performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complaints of difficulty in finding words are common in the elderly, and are even more common and challenging in elderly individuals with MCI [2,3]. However, studies of the differences in performance between individuals with MCI and healthy elderly (HE) subjects have reported mixed findings [4,5,6,7,8,9,10,11,12,13,14]. Evaluation of naming ability in individuals with MCI requires the consideration of a number of factors and characteristics affecting performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews have yielded evidence supporting the existence of noun naming deficits in individuals with MCI [10,14]. However, individual studies have revealed contradictory results: while some studies suggest that individuals with MCI performed significantly more poorly on the BNT than HE subjects [4,5,6,7,8,9,11,12,13], other studies did not find significant differences between the two groups [10,25,26,27,28,29,30,31,32]. These inconsistent reports about the performance on BNT in MCI can be explained by differences in the diagnostic criteria, procedural differences in the naming tasks, and the possibility that only a segment of patients with MCI has naming deficits [33].…”
Section: Introductionmentioning
confidence: 99%
“…다음으로 레비소체치매(dementia with Lewy bodies)나 전두측두엽 변성(frontotemporal degeneration)과 같은 비알츠하 이머형 치매로의 진행 가능성이 높고, aMCI와 달리 기억력 이외의 다른 인지기능 손상이 두드러진 비기억상실형 경도인지장애(nonamnestic mild cognitive impairment, non-aMCI)가 있다 (Fischer et al, 2007). 이렇듯 MCI는 다양한 양상의 인지 손상을 보이는 이 질적인 집단이므로, 최근 연구들은 MCI 하위유형의 특성을 보다 구체적으로 살펴보고 있다 (Devanand et al, 2010;Jefferson et al, 2006;Weakley, Schmitter-Edgecombe, & Anderson, 2013 (Adlam et al, 2006;Beinhoff, Hilbert, Bittner, Gron, & Riepe, 2005;Duong et al, 2006;Hwang & Kim, 2014), 그 차이가 유의하지 않다는 연구결과 (Balthazar et al, 2008;Choi, Kim, Lee, & Kim, 2013;Deason, Hussey, Budson, & Ally, 2012;Jourbert et al, (Adlam et al, 2006;Vliet et al, 2003) 세분화된 경우에도 대부분 aMCI 환자 를 대상으로 하고 있다 (Balthazar et al, 2008;Deason et al, 2012;Duong et al, 2006;Jourbert et al, 2010). 둘째, 연구에서 활용된 대 면이름대기 과제의 특성이 연구결과에 영향을 미칠 수 있다.…”
unclassified